What counts as learning in play? Uncovering patterns in perceptions of South African early educators. Issue 3 (3rd July 2021) - Jensen, Hanne; Kvalsvig, Jane Dene; Taylor, Myra; Sibisi, Snenhlanhla; Whitebread, David; McLellan, Ros
ABSTRACT: Early educators' perceptions of play and learning influence whether they adopt responsive roles to facilitate learning in play. While studies have investigated perceptions of play as pedagogical practice and its perceived relevance for learning, few have also interrogated educator learning perceptions, and hence compared these perceptions. This study explored perceptions among South African early educators by contrasting their interview and questionnaire responses. Findings revealed play perceptions encompassing structured, adult-led activities alongside child-managed play. While play was highlighted as active, joyful and chosen, participants emphasised appropriate, real-world play over children's self-directed explorations and make-believe. Learning perceptions presented a span that primarily centred on correctness, followed by children understanding and applying lessons. Surprisingly, less nuance emerged for learning in play: rather than viewing play as a context for practicing and improving, respondents saw play as a 'stage' where children could demonstrate proficiency. Finally, patterns in play and learning perceptions came out more clearly in interviews than the questionnaire. These findings point to a need for alternative at-scale methods when eliciting educator perceptions, and for supporting educators to develop reflected, nuanced notions of play as practice and children's learning in play.